Electrode material and method for manufacturing the same, and electrode, membrane electrode assembly and polymer electrolyte fuel cell using the same
By using a Ta oxide support to immobilize the PEFC electrode material on the porous carbon surface, the problems of carbon-based support oxidation and Pt particle aggregation are solved, and the high corrosion resistance and long-term stability of the electrode are achieved.
Patent Information
- Application Number
- JP2023175261
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-10-10
- Publication Date
- 2025-04-22
- Estimated Expiration
- 2043-10-10
AI Technical Summary
When existing PEFC electrode materials are used in acidic environments, the carbon-based support is prone to oxidation, resulting in corrosion of carbon compounds and aggregation and shedding of Pt particles, affecting the long-term stability and performance of the electrode.
Porous carbon with Ta oxide support is used as the carrier of the electrode material, and Ta oxide is fixed on the inner and outer surfaces of the porous carbon and supports Pt or Pt alloy particles on its surface, thereby reducing the direct contact between Pt and carbon and avoiding carbon corrosion.
It improves the corrosion resistance and durability of the electrode, reduces the aggregation and fall of Pt particles, maintains efficient electrochemical performance, and maintains good performance even under repeated start and stop conditions.
Smart Images

Figure 2025065809000001_ABST
Abstract
Description
[Technical field]
[0001] The present invention relates to an electrode material suitable for electrodes of polymer electrolyte fuel cells, and to an electrode, a membrane electrode assembly, and a polymer electrolyte fuel cell each using the electrode material. [Background technology]
[0002] Fuel cell vehicles (FCVs) that use polymer electrolyte fuel cells (PEFCs) as their power source are already commercially available, and it is expected that their applications will expand and become more widespread in trucks, buses, ships, and other vehicles in the future. PEFCs generally have a structure in which a membrane electrode assembly (MEA), in which a pair of electrodes are arranged on both sides of a solid polymer electrolyte membrane, is sandwiched between separators with gas flow paths. Fuel cell electrodes (particularly PEFC electrodes) generally consist of an electrode catalyst layer made of an electrode material with electrocatalytic activity and a polymer electrolyte, and a gas diffusion layer that combines gas permeability and electronic conductivity.
[0003] Currently, electrode materials in widespread use for PEFCs are those in which electrode catalyst fine particles (typically Pt or Pt alloy fine particles) are dispersed and supported on a carbon-based support. In recent years, electrode materials in which mesoporous carbon is used as the framework of the catalyst support and Pt fine particles are supported within the pores (mesopores) of the mesoporous carbon have attracted attention (e.g., Patent Documents 1 and 2). Mesoporous carbon has excellent electrical conductivity, is easy to diffuse gases, and has a large surface area, so that when it is used as a support for the electrode catalyst of a polymer electrolyte fuel cell, an electrode with excellent power generation performance can be obtained.
[0004] Furthermore, Patent Document 3 discloses a method for producing an electrode material, in which mesoporous carbon is contacted with a tin oxide precursor compound in a solution, the solvent is then distilled off to obtain a dried product, and the resulting product is heat-treated at 350° C. or higher and 700° C. or lower in a nitrogen atmosphere to obtain a porous composite support on which Pt particles are supported. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] Patent No. 6969996 [Patent Document 2] Patent No. 6931808 [Patent Document 3] JP 2023-101475 A Summary of the Invention [Problem to be solved by the invention]
[0006] Incidentally, since the electrolyte membrane of a PEFC is acidic (pH=0-3), the electrode material of the PEFC is used in an acidic atmosphere. In addition, the cell voltage during normal operation is 0.4-1.0V, but it is known that the cell voltage rises to 1.5V during start-up and shutdown. The state of the cathode and anode under such PEFC operating conditions is a region in which the carbon-based material, which is the carrier, is oxidized and carbon dioxide (CO2) is stable. Therefore, in the cathode, a reaction occurs in which the carbon-based carrier is electrochemically oxidized to generate CO2, resulting in corrosion of the carbon-based carrier (carbon corrosion), which causes aggregation and detachment of Pt particles, which are catalytically active components, and causes a decrease in the performance of the fuel cell. In addition, if the fuel gas is insufficient not only in the cathode but also in the anode at the beginning of operation, a voltage drop or concentration polarization occurs in that part, resulting in a localized potential opposite to normal, and an electrochemical oxidation and decomposition reaction of carbon may occur.
[0007] The electrode materials disclosed in Patent Documents 1 and 2, in which Pt microparticles are supported within the pores (mesopores) of mesoporous carbon, are said to be less susceptible to aggregation of the Pt microparticles. However, because the Pt microparticles are supported in direct contact with the pore walls of the mesoporous carbon, carbon corrosion is unavoidable, and there is a problem in that it is impossible to prevent aggregation and falling off of the Pt particles due to carbon corrosion when generating electricity for a long period of time.
[0008] Furthermore, the electrode material disclosed in Patent Document 3 has a structure in which tin oxide is fixed to the inner and outer pore surfaces of mesoporous carbon, and Pt particles are supported on the fixed tin oxide. Such an electrode structure has the advantage that the number of Pt particles in direct contact with the surface of the mesoporous carbon is reduced, making the above-mentioned carbon corrosion less likely to occur. However, there is a problem in that Pt and Sn form an alloy during the manufacture of the electrode material or during the operation of the fuel cell, resulting in a decrease in performance.
[0009] Under these circumstances, an object of the present invention is to provide an electrode material that provides a fuel cell electrode having excellent electrode performance and durability, a method for producing the same, and an electrode, a membrane electrode assembly, and a solid polymer electrolyte fuel cell that use the same. [Means for solving the problem]
[0010] As a result of intensive research aimed at solving the above problems, the present inventors discovered that the following invention meets the above object, and thus completed the present invention.
[0011] That is, the present invention relates to the following inventions. <1> The present invention includes a porous composite support including a support skeleton made of porous carbon, a Ta oxide support fixed to at least the inner pore surfaces of the inner pore surfaces and the outer pore surfaces of the porous carbon, and electrode catalyst particles supported on the porous composite support, An electrode material in which a part or all of the electrode catalyst particles are supported within the pores of the porous carbon via the Ta oxide support. <2> The Ta oxide support contains a crystalline Ta oxide. <1> The electrode material according to claim 1. <3> The Ta oxide support is a Ta oxide support containing an oxygen-deficient Ta oxide. <2> The electrode material according to claim 1. <4> The Ta oxide support is a Ta oxide support containing TaO. <2> The electrode material according to claim 1. <5> The porous carbon is mesoporous carbon. <1> from <4> 13. The electrode material according to claim 12, <6> The pore size of the mesoporous carbon is 3 nm or more and 40 nm or less. <5> The electrode material according to claim 1. <7> The electrode catalyst particles are particles made of Pt or an alloy containing Pt. <1> from <6> 13. The electrode material according to claim 12, <8> <1> from <7> 13. An electrode comprising the electrode material according to any one of claims 1 to 12 and a proton-conducting electrolyte material. <9> A membrane electrode assembly having a solid polymer electrolyte membrane, a cathode bonded to one side of the solid polymer electrolyte membrane, and an anode bonded to the other side of the solid polymer electrolyte membrane, wherein either or both of the anode and the cathode are <8> A membrane electrode assembly comprising the electrode according to claim 1. <10> <9> 2. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 1.
[0012] <1a> <1> from <7> 2. A method for producing the electrode material according to any one of the above, comprising the following steps (1) to (3): Step (1): A step of mixing porous carbon and tantalum alkoxide in a non-aqueous organic solvent, and then distilling off the solvent to obtain a dried product in which tantalum alkoxide is fixed to the inner and outer pore surfaces of the porous carbon. Step (2): A step of hydrolyzing the tantalum alkoxide by steam-treating the dried product obtained in step (1), and then performing heat treatment to obtain a porous composite support in which the Ta oxide support is fixed to the inner and outer pore surfaces of the porous carbon. Step (3): A step of mixing the porous composite support obtained in step (2) with a solution containing an electrode catalyst precursor, and then heat-treating the dried product obtained by distilling off the solvent to produce electrode catalyst particles. <2a> The method for producing an electrode material according to <1a>, wherein in the step (1), the tantalum alkoxide is tantalum ethoxide. <3a> The method for producing an electrode material according to <1a> or <2a>, wherein in the step (2), the heat treatment is carried out in a hydrogen atmosphere. <4a> The method for producing an electrode material according to <3a>, wherein the heat treatment temperature in a hydrogen atmosphere is 650° C. or higher. <5a> The method for producing an electrode material according to <1a> or <2a>, wherein in the step (2), the heat treatment is carried out in an inert gas atmosphere. <6a> The method for producing an electrode material according to <5a>, wherein the heat treatment temperature in an inert gas atmosphere is 1100° C. or higher. <7a> The method for producing an electrode material according to <5a> or <6a>, wherein the inert gas is Ar. <8a> The method for producing an electrode material according to any one of <1a> to <7a>, wherein in the step (3), the electrode catalyst precursor is a noble metal acetylacetonate. <9a> The method for producing an electrode material according to any one of <1a> to <7a>, wherein in the step (3), the method for supporting the electrode catalyst precursor is a colloidal method. Effect of the Invention
[0013] According to the present invention, there are provided an electrode material that provides a fuel cell electrode having excellent electrode performance and durability, a method for producing the same, and an electrode, a membrane electrode assembly, and a polymer electrolyte fuel cell that use the same. [Brief description of the drawings]
[0014] [Figure 1] FIG. 2(a) is a conceptual schematic diagram of an example of an electrode material of the present invention, and FIG. 2(b) is an enlarged schematic diagram of the vicinity of a pore. [Diagram 2] 1 is a schematic cross-sectional view of a membrane electrode assembly of the present invention. [Diagram 3] FIG. 1 is a conceptual diagram showing a typical configuration of a polymer electrolyte fuel cell according to the present invention. [Figure 4] 1 is a flowchart showing a procedure for preparing an electrode material (TaOx / MC, no electrode catalyst supported) in an experimental example. [Diagram 5] 1 is a flowchart of a procedure for producing an electrode material (Pt / TaOx / MC) in an experimental example. [Figure 6] 1 shows the results of X-ray diffraction (XRD) measurement of the electrode materials of Experimental Examples 1 to 4 (electrode catalyst unsupported, H2 treatment). [Figure 7]1 is a field emission scanning electron microscope (FESEM) image of the electrode material of Experimental Example 1 (electrode catalyst not supported, H2 treatment at 500°C). [Figure 8] 1 is an FESEM image of the electrode material of Experimental Example 2 (electrode catalyst not supported, H2 treatment at 600°C). [Figure 9] 1 is an FESEM image of the electrode material of Experimental Example 3 (electrode catalyst not supported, H2 treatment at 700°C). [Figure 10] 1 is an FESEM image of the electrode material of Experimental Example 4 (electrode catalyst not supported, H2 treatment at 800°C). [Figure 11] 1 is a scanning transmission electron microscope (STEM) image of the electrode material of Experimental Example 3 (electrode catalyst not supported, H2 treatment at 700°C). [Figure 12] 1 shows energy dispersive X-ray analysis (EDS) mapping and selected area electron diffraction pattern (SAEDP) of the electrode material of Experimental Example 3 (electrode catalyst not supported, H2 treatment at 700°C). [Figure 13] 1 shows the results of XRD measurement of the electrode materials of Experimental Examples 5 to 11 (electrode catalyst not supported, Ar treatment). [Figure 14] 1 is an FESEM image of the electrode material of Experimental Example 6 (electrode catalyst not supported, Ar treatment at 900° C.). [Figure 15] 1 is an FESEM image of the electrode material of Experimental Example 8 (electrode catalyst not supported, Ar treatment at 1100° C.). [Figure 16] 1 is an FESEM image of the electrode material of Experimental Example 10 (electrode catalyst not supported, Ar treatment at 1300° C.). [Figure 17] 1 shows EDS mapping and SAEDP of the electrode material of Experimental Example 10 (electrode catalyst not supported, Ar treatment at 1300° C.). [Figure 18] 1 shows the results of EDS line analysis of the electrode material of Experimental Example 10 (electrode catalyst not supported, Ar treatment at 1300° C.). [Figure 19] FIG. 1 is a diagram showing the electrochemically effective surface area (ECSA) of the electrode material (Pt / TaOx / MC, H2 treatment) of Experimental Examples 1 to 4, the comparative example (Pt / MC), and the reference example (Pt / C). [Figure 20]FIG. 1 shows ECSA of the electrode material (Pt / TaOx / MC, Ar treatment) of Experimental Examples 5 to 11, the comparative example (Pt / MC), and the reference example (Pt / C). [Figure 21] FIG. 1 is a graph showing the mass activity (0.9VRHE) of the electrode material (Pt / TaOx / MC, H2 treatment) of Experimental Examples 1 to 4, the comparative example (Pt / MC), and the reference example (Pt / C). [Figure 22] FIG. 1 is a graph showing the mass activity (0.9VRHE) of the electrode material (Pt / TaOx / MC, Ar treatment) of Experimental Examples 5 to 11, the comparative example (Pt / MC), and the reference example (Pt / C). [Figure 23] FIG. 13 is a diagram showing conditions of a start-stop cycle test. [Figure 24] FIG. 13 is a graph showing the relationship between the number of start-stop cycle tests and ECSA for the electrode materials of Experimental Example 3 (H2 treatment, 700° C.), Experimental Example 10 (Ar treatment, 1300° C.), and Comparative Example (Pt / MC). [Diagram 25] FIG. 13 is a diagram showing conditions of a load change cycle test. [Figure 26] FIG. 13 is a graph showing the relationship between the number of load change cycle tests and ECSA for the electrode materials of Experimental Example 3 (H2 treatment, 700° C.), Experimental Example 10 (Ar treatment, 1300° C.), and Reference Example (Pt / C). [Figure 27] 1 is a transmission electron microscope (TEM) image of the electrode material of Experimental Example 3 (H2 treatment, 700°C) after a load change cycle test (10 cycles). [Figure 28] 1 is a transmission electron microscope (TEM) image of the electrode material of Experimental Example 10 (Ar treatment, 1300° C.) after a load change cycle test (10 cycles). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will be described in detail below with reference to examples, but the present invention is not limited to the following examples, and can be modified as desired without departing from the gist of the present invention. In this specification, the word "to" is used as an expression including the numerical values or physical quantities before and after it.
[0016] (Definition of Terms, etc.) In this specification, "porous carbon" means a "carbon material having a plurality of pores" that serves as the backbone (base) of the electrode material. In this specification, "pores" include, for example, pores with a diameter of 150 nm or less (especially pores with a diameter of 100 nm or less). "Pores in the mesopore region" means pores with a diameter of 2 nm to 50 nm. Also, in this specification, "pores in the micropore region" means pores with a diameter of less than 2 nm, and "pores in the macropore region" means pores with a diameter of more than 50 nm and 150 nm or less.
[0017] Also, in this specification, "Ta oxide" means an oxide of tantalum (Ta), and the form of Ta oxide is not limited to crystals, but includes any of crystals, amorphous substances, and mixtures of crystals and amorphous substances. When distinguishing and representing Ta oxide as crystalline and amorphous, they shall be represented as "crystalline Ta oxide" and "amorphous Ta oxide", respectively. Note that in this specification, "crystalline Ta oxide" is a concept that includes not only the crystals of Ta2O5 (TaOx, x = 2.5), which is the most stable oxide, but also the crystals of oxygen-deficient oxides (TaOx, 0.1 < x < 2.5).
[0018] Also, in this specification, the cathode conditions of a polymer electrolyte fuel cell (PEFC) are the conditions at the cathode during normal operation of the PEFC, which means conditions where the temperature is about room temperature to 150°C and a gas containing oxygen such as air is supplied (oxidizing atmosphere), and the anode conditions are the conditions at the anode during normal operation of the PEFC, which means conditions where the temperature is about room temperature to 150°C and a fuel gas containing hydrogen is supplied (reducing atmosphere).
[0019] <1. Electrode Material> The present invention includes a porous composite carrier composed of a carrier skeleton made of porous carbon and a Ta oxide carrier fixed to at least the inner surface of the pores among the inner and outer surfaces of the pores of the porous carbon, and electrode catalyst particles supported on the porous composite carrier. The present invention relates to an electrode material in which a part or all of the electrode catalyst particles are supported in the pores of the porous carbon via the Ta oxide support (hereinafter, referred to as "the electrode material of the present invention").
[0020] In this specification, "fixed" means that the Ta oxide support is fixed to the inner and outer pore surfaces of the porous carbon, which is the support skeleton, to an extent that it does not easily detach (peel off).
[0021] In the electrode material of the present invention, the Ta oxide support is fixed so as to cover a part or the whole of the inner surface of the pores in the porous carbon, and the electrode catalyst particles are supported on the Ta oxide support. That is, the electrode catalyst particles are supported in the pores of the porous carbon via the Ta oxide support. Note that in the electrode material of the present invention, the electrode catalyst particles may be supported not only inside the pores but also on the outer surfaces of the pores.
[0022] The form of the Ta oxide support fixed to the surface of the porous carbon may be any of particulate, island, thin film, etc., as long as it does not impair the object of the present invention. "Island" means a state in which several particulate Ta oxide support particles are aggregated and separated from each other, and "film" means a state in which the Ta oxide support is continuously connected to form a thin film.
[0023] The electrode material of the present invention is suitable as an electrode material for use in electrodes for polymer electrolyte fuel cells, but can also be used for other purposes (for example, electrodes for polymer electrolyte water electrolysis).
[0024] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Preferred embodiments of the present invention will now be described in detail with reference to the drawings. In the following, the electrode material of the present invention will be described assuming its use in an electrode for a polymer electrolyte fuel cell (PEFC).
[0025] FIG. 1(a) is a schematic diagram showing a typical structure of an electrode material of the present invention, and FIG. 1(b) is an enlarged schematic diagram of the vicinity of a pore.
[0026] As shown in Figures 1(a) and (b), an electrode material 1 according to the present invention is composed of a porous composite support made of porous carbon 2, which is a support skeleton, and particulate Ta oxide support 3a fixed to the porous carbon 2 (pore inner surfaces 2a and outer surfaces 2b), and electrode catalyst particles 3b supported on the Ta oxide support 3a.
[0027] The electrode material 1 shown in Figures 1(a) and (b) has the Ta oxide support 3a and the electrode catalyst particles 3b dispersed and supported thereon also on the outer surface 2b, but the Ta oxide support 3a and the electrode catalyst particles 3b may be present only on the inner surface 2a of the pores.
[0028] The porous carbon 2 which is the support skeleton of the electrode material 1 (hereinafter, may be referred to as "porous carbon according to the present invention") is porous carbon having a large number of pores.
[0029] The porous carbon is preferably porous carbon having a plurality of pores forming a three-dimensional network structure. Here, "having a plurality of pores forming a three-dimensional network structure" means that the porous carbon has a plurality of pores on the surface and inside thereof, adjacent pores are connected to each other, and thus the plurality of pores are three-dimensionally connected, and continuous pores having openings on the surface are formed.
[0030] The pore structure (pore size, shape, etc.) of the porous carbon can be confirmed by observation with an electron microscope, such as a field emission scanning electron microscope (FESEM), a transmission electron microscope (TEM), or a scanning transmission electron microscope (STEM).
[0031] The size and shape of the electrode material 1 depend on the size and shape of the porous carbon that is its framework material. The size and shape of the porous carbon are determined so that the electrode material can be in continuous contact when the electrode for the fuel cell is formed, and a space can be formed that allows the diffusion of gases such as hydrogen and oxygen and the discharge of water (steam) in the electrode for the fuel cell to be performed smoothly.
[0032] Carbon materials of any shape and size, such as granular or fibrous, that can be used as an electrode material for a fuel cell can be used as the porous carbon 2. Examples of carbon materials include particulate carbon such as carbon black and activated carbon (including chain-linked carbon particles), and mesoporous carbon.
[0033] The porous carbon used in the present invention may be one type, or two or more types of carbon materials differing in size (particle size, fiber diameter, and fiber length), crystallinity, etc. may be used in any ratio.
[0034] One suitable example of the porous carbon is mesoporous carbon. The mesoporous carbon according to the present invention may contain regions (micropore region, macropores) other than the mesopore region (2 nm to 50 nm) pores, but it is preferable that the proportion of pores in the mesopore region is high.
[0035] The pores in the mesopore region of the mesoporous carbon preferably have a three-dimensional network structure, including not only individual pores independent of other pores, but also interconnected pores in which some or all of the pores in the mesopore region are interconnected with the pores in adjacent mesopore regions. The presence of interconnected pores promotes the diffusion of substances within the pores of the mesoporous carbon.
[0036] The mesoporous carbon according to the present invention has pores with a diameter of 2 nm to 50 nm (preferably 3 nm to 40 nm). If the pore diameter is within this range, even if a Ta oxide support or an electrode catalyst is fixed (supported) on the inner wall of the pore, the diffusion of substances into the pores is not significantly hindered and proceeds smoothly.
[0037] In addition, as described later, when preparing an electrode for a fuel cell, the electrode material of the present invention is mixed with a proton-conductive electrolyte material (ionomer). Since the proton-conductive electrolyte material (ionomer) cannot penetrate into small-diameter pores, it is possible to suppress poisoning of the electrode catalyst particles supported in the pores of the porous carbon via the Ta oxide carrier, which is caused by the ionomer.
[0038] The mesoporous carbon used in the electrode material of the present invention may be appropriately synthesized or may be a commercially available product, such as the CNovel series (designed mesopore diameter: 5 to 30 nm) manufactured by Toyo Tanso Co., Ltd., which is a mesoporous carbon using MgO as a template.
[0039] Another suitable example of the porous carbon is particulate solid carbon. As the solid carbon, carbon black (Carbon Black, CB) or highly crystalline carbon black (Graphitized Carbon Black, GCB) obtained by graphitizing (crystallizing) carbon black can be suitably used. The particulate solid carbon preferably has a secondary particle diameter of 0.03 to 500 μm (primary particle diameter of about 10 nm to 100 nm).
[0040] Solid carbon can be either homemade or commercially available. Examples include the "Ketjen Black" series (product number: EC600JD, etc.) from Lion Specialty Chemicals Co., Ltd., the "Vulcan" series (product number: XC-72, etc.) from Cabot Corporation, the "GCB" series (product number: GCB200, etc.) from Cabot Corporation, the "Toka Black" series (product number: Toka Black #3800, etc.) from Tokai Carbon Co., Ltd., and the "Denka Black" series (product number: OSAB, Li-435, etc.) from Denka Co., Ltd.
[0041] (Ta oxide support) 1, in the electrode material 1 of this embodiment, the Ta oxide support 3a is fixed to the inner surface 2a of the pores in the porous carbon 2. In the electrode material 1 of this embodiment, the Ta oxide support 3a is also fixed to the outer surface 2b of the porous carbon 2, but the Ta oxide support 3a on the outer surface 2b is not necessarily required.
[0042] The Ta oxide that constitutes the Ta oxide support is an oxide of tantalum (Ta). Unlike carbon materials, the Ta oxide support does not decompose by oxidation, so durability is improved by supporting the electrode catalyst particles on the Ta oxide support and preventing them from coming into direct contact with the porous carbon.
[0043] As the Ta oxide constituting the Ta oxide carrier, any Ta oxide having sufficient durability and electron conductivity under at least one of the anode conditions and cathode conditions of the PEFC may be used.
[0044] The Ta oxide carrier may be only a crystalline Ta oxide, only an amorphous Ta oxide, or a mixture of a crystalline Ta oxide and an amorphous Ta oxide.
[0045] The crystallinity of the Ta oxide carrier can be evaluated, for example, by X-ray diffraction (XRD) or transmission electron microscopy (TEM).
[0046] The Ta oxide carrier preferably contains a crystalline Ta oxide in an oxygen-deficient state. The oxygen-deficient Ta oxide is a Ta oxide in which oxygen is deficient from Ta2O5 (TaOx (x = 2.5)), which is the most stable oxide, and can be expressed as TaOx (0.1 <x <2.5). Since the oxygen-deficient Ta oxide has better electron conductivity than Ta2O5, the electrode performance tends to be improved by using it as the Ta oxide carrier.
[0047] The range of x in the oxygen-deficient Ta oxide (TaOx) may be in the range of 0.1 <x <2.5 and there is no limitation as long as the object of the present invention is not impaired. For example, 0.5 <x <1.5 (including TaO where TaOx (x = 1)) and 1.5 <x <2.4 (including TaO2 where TaOx (x = 2)) can be mentioned.
[0048] A preferred example of the Ta oxide carrier is a Ta oxide carrier containing TaO. Although the detailed mechanism is unclear at present, when the Ta oxide carrier contains TaO crystals, as shown in the examples, the mass activity (current value per unit mass of electrode catalyst particles) is improved, and the durability during startup and shutdown of the fuel cell and during load fluctuations is improved. The Ta oxide carrier containing TaO can be formed, for example, by heat treatment (1100 ° C or higher) in an inert gas atmosphere as described later.
[0049] The amount of Ta oxide support adhered to the porous carbon is appropriately determined taking into consideration the crystallinity (crystalline, amorphous), degree of oxygen deficiency and form (particulate, film, etc.) of the Ta oxide support, and the physical properties (pore distribution, specific surface area, etc.) of the porous carbon. The amount of Ta oxide adhered to the support is, for example, 5 to 95% by weight, or 20 to 60% by weight, when the total amount of the porous carbon and the Ta oxide support is 100% by weight. If the amount of the Ta oxide support is too small, the amount of the electrode catalyst supported thereon will be small, resulting in insufficient electrode performance, whereas if the amount is too large, a large amount of the Ta oxide adheres to the outside of the pores of the porous carbon, and may aggregate, resulting in reduced performance. The amount of Ta oxide adhering to the support can be examined by, for example, inductively coupled plasma emission spectrometry (ICP).
[0050] The optimal amount of the Ta oxide support varies depending on the physical properties of the Ta oxide support, such as particle size (film thickness if it is a thin film) and surface area, and on the method of manufacturing the Ta oxide support. Therefore, the amount of the Ta oxide support is appropriately determined within a range in which a sufficient amount of electrode catalyst particles can be supported.
[0051] The size of the Ta oxide support in the pores is determined within a range that does not block the pores of the porous carbon 2 and does not inhibit the transfer of substances such as gas. Although it depends on the pore size of the porous carbon 2, the size of the Ta oxide support fixed to the inner surface of the pores is preferably an average particle size of 0.5 nm or more and 7 nm or less.
[0052] The Ta oxide support on the outer surface may be larger than the Ta oxide support inside the pores because it is not substantially involved in blocking the pores, but in order to reduce electrical resistance, it is preferable that the particle size is small within a range in which the electrode catalyst particles can be dispersed and supported. When a Ta oxide support is provided on the outer surface, the size of the Ta oxide support is preferably an average particle size of 0.5 nm or more and 10 nm or less.
[0053] The "average particle size of the Ta oxide support" can be obtained by averaging the particle sizes of any particulate Ta oxide support (20 particles) examined from an electron microscope image.
[0054] 1, the Ta oxide support 3a is a particulate Ta oxide support dispersed and fixed in the porous carbon 2, but is not limited thereto, and it is sufficient that the Ta oxide support 3a is fixed to the porous carbon 2. For example, the particulate Ta oxide support 3a may not be dispersed but may be continuously fixed to the surface of the porous carbon 2 (particularly the inner surface of the pores) so as to coat the surface in a thin film.
[0055] (electrode catalyst particles) As shown in Fig. 1, the electrode catalyst particles 3b are dispersed and supported on the Ta oxide support 3a. The ratio of electrode catalyst particles supported on the Ta oxide support can be evaluated by selecting any electrode catalyst particles (100 or more) observed under an electron microscope from the electrode material to be evaluated, and counting the number of particles supported on the Ta oxide support and the number of particles supported on the porous carbon.
[0056] The electrode catalyst particles may be either a precious metal catalyst or a non-precious metal catalyst as long as they have electrochemical catalytic activity for the reduction of oxygen (and the oxidation of hydrogen), but are preferably selected from precious metals such as Pt, Ru, Ir, Pd, Rh, Os, Au, and Ag, and alloys containing these precious metals. The term "alloy containing a precious metal" includes "alloys consisting of only the above-mentioned precious metals" and "alloys consisting of the above-mentioned precious metals and other metals and containing 10 mass % or more of the above-mentioned precious metals". The "other metals" to be alloyed with the precious metal are not particularly limited, but suitable examples include Co, Ni, and Ta, and one or more of these may be used. In addition, two or more of the above-mentioned precious metals and alloys containing the precious metals in a phase-separated state may be used. In this specification, the above-mentioned precious metals and alloys containing these precious metals may be referred to as "electrode catalyst metals" hereinafter.
[0057] Among the electrode catalyst metals, Pt and alloys containing Pt (Pt alloys) are particularly suitable for use because they have high electrochemical catalytic activity for the reduction of oxygen (and the oxidation of hydrogen) in the temperature range around 80°C, which is the operating temperature of solid polymer electrolyte fuel cells. The metal species other than Pt in the Pt alloy is not particularly limited as long as it can form an alloy, but is preferably cobalt (Co).
[0058] The shape of the electrode catalyst particles is not particularly limited, and any shape similar to that of known electrode catalyst particles can be used. Specific shapes include a sphere, an ellipse, a polyhedron, a core-shell structure, etc. In addition, the structure of the electrode catalyst particles is not limited to a crystal, and may be amorphous or a mixture of a crystal and an amorphous structure.
[0059] The smaller the size of the electrode catalyst particles, the greater the effective surface area for the electrochemical reaction to proceed, and therefore the higher the electrochemical catalytic activity tends to be. However, if the size is too small, the electrochemical reaction activity decreases. Therefore, the size of the electrode catalyst particles is preferably 0.5 to 4 nm as the average particle size.
[0060] In the present invention, the "average particle size of electrode catalyst particles" can be obtained by averaging the particle sizes of electrode catalyst particles (20 particles) examined from an electron microscope image. When calculating the average particle size from an electron microscope image, if the shape of the fine particles is other than spherical, the length in the direction showing the maximum length of the particle is taken as the particle size.
[0061] The amount of electrode catalyst particles supported is appropriately determined taking into consideration the type of catalyst, the size (thickness) of the Ta oxide support, and other conditions. The amount of electrode catalyst particles supported is, for example, 0.1 to 60 mass%, or 0.5 to 20 mass%, relative to the total weight of the electrode material. Within such a range, excellent catalytic activity per unit mass can be obtained, and a desired electrode reaction activity according to the amount supported can be obtained. If the amount of catalyst supported is too small, the electrode performance will be insufficient, and if it is too large, the electrode catalyst particles may aggregate and performance may decrease. The amount of electrode catalyst particles supported can be examined, for example, by inductively coupled plasma emission spectrometry (ICP).
[0062] The amount of the electrode catalyst particles supported is usually 3 to 40 mass% based on the Ta oxide support. Within this range, excellent catalytic activity per unit mass can be obtained, and a desired electrochemical catalytic activity according to the supported amount can be obtained. The amount of electrode catalyst particles supported can be examined, for example, by inductively coupled plasma emission spectrometry (ICP).
[0063] <2. Manufacturing method of electrode material> The method for producing the electrode material of the present invention described above is not particularly limited, and a suitable method may be selected depending on the types of porous carbon, Ta oxide support, and electrode catalyst particles that constitute the electrode material of the present invention. Typically, a method is employed in which a Ta oxide support is supported on porous carbon, and then the electrode catalyst particles are supported on the Ta oxide support.
[0064] A suitable example of the method for producing the electrode material of the present invention is a production method including steps (1) to (3) described below (hereinafter, sometimes referred to as the "method for producing the electrode material of the present invention" or simply the "production method of the present invention"). According to the method for producing an electrode material of the present invention, it is possible to reliably fix the Ta oxide support within the pores of the porous carbon that is the support skeleton, and to support electrode catalyst particles thereon.
[0065] Step (1): A step of mixing porous carbon and tantalum alkoxide in a non-aqueous organic solvent, and then distilling off the solvent to obtain a dried product in which tantalum alkoxide is fixed to the inner and outer pore surfaces of the porous carbon. Step (2): A step of hydrolyzing the tantalum alkoxide by steam-treating the dried product obtained in step (1), and then performing heat treatment to obtain a porous composite support in which the Ta oxide support is fixed to the inner and outer pore surfaces of the porous carbon. Step (3): A step of mixing the porous composite support obtained in step (2) with a solution containing an electrode catalyst precursor, and then heat-treating the dried product obtained by distilling off the solvent to produce electrode catalyst particles.
[0066] The method for producing the electrode material of the present invention will be described in detail below.
[0067] Step (1) is a step of mixing porous carbon and tantalum alkoxide in a non-aqueous organic solvent, and then distilling off the solvent to obtain a dried product in which tantalum alkoxide is adhered to the inner and outer pore surfaces of the porous carbon.
[0068] As described above, porous carbon has many pores into which an aqueous solvent is unlikely to penetrate, but an alkoxide compound can be made to penetrate into the pores by using a nonaqueous organic solvent. Therefore, an alkoxide compound is used as a raw material, which is dissolved and mixed with porous carbon in a nonaqueous organic solvent, and the nonaqueous organic solvent is distilled off to dry the alkoxide compound in a state where it is adsorbed on the surface of the porous carbon (particularly the inner surface of the pores).
[0069] As the tantalum alkoxide, tantalum methoxide, tantalum ethoxide, tantalum propoxide, tantalum butoxide, tantalum methoxyethoxide, and tantalum ethoxyethoxide can be used. Among these, tantalum ethoxide is preferred.
[0070] The non-aqueous organic solvent may be any solvent with which the alkoxide compound does not react, and examples thereof include acetone, acetylacetone, toluene, xylene, and kerosene. It is preferable that the non-aqueous organic solvent is substantially free of water. Here, "substantially free of water" does not exclude the presence of even a trace amount of water as an impurity contained in a hydrophilic solvent, but includes the case where a person skilled in the art has made an effort to reduce the water content in the solvent as much as possible by ordinary industrial efforts.
[0071] The concentrations of the porous carbon and tantalum alkoxide may be appropriately determined within ranges that allow the production of the electrode material of the present invention.
[0072] The method for distilling off the solvent may be any method as long as it does not impair the object of the present invention, but distilling off the solvent under reduced pressure is preferred.
[0073] In step (2), the dried product obtained in step (1) is treated with water vapor to hydrolyze the tantalum alkoxide, and then a heat treatment is performed to obtain a porous composite support in which the Ta oxide support is fixed to the inner and outer surfaces of the pores of the porous carbon.
[0074] In step (2), the dried product obtained in step (1) is first treated with steam to hydrolyze the alkoxide compound adsorbed on the surface (inner and outer surfaces of the pores). Here, "steam treatment" means contacting with a gas containing steam to cause a reaction. The gas used in the steam treatment is an inert gas such as nitrogen, helium, or argon, and is usually nitrogen.
[0075] The gas used for the water vapor treatment preferably contains 0.5 to 90% (preferably 1 to 20%) water vapor.
[0076] After hydrolysis by steam treatment, the hydrolyzate of the alkoxide compound (mainly hydroxide) is converted into the desired Ta oxide support by heat treatment.
[0077] One of the features of the method for producing an electrode material of the present invention is the method for heat treating the hydrolysate of the alkoxide compound. An example of a suitable heat treatment method is a method in which the heat treatment in step (2) is performed in a hydrogen atmosphere (H2 treatment). When the heat treatment in step (2) is performed in a hydrogen atmosphere, the heat treatment temperature is 400°C or higher, preferably 650°C or higher, and more preferably 700°C or higher. By carrying out a heat treatment in a hydrogen atmosphere (H2 treatment) at 650°C or higher, a Ta oxide support containing Ta2O5, which is a crystalline Ta oxide, can be obtained. As shown in the examples, when the Ta oxide support contains Ta2O5 produced by H2 treatment, it is possible to obtain an electrode material that can provide an electrode with excellent performance (particularly mass activity).
[0078] If the temperature becomes too high in a hydrogen atmosphere, the porous carbon may decompose, the mechanical strength may decrease, and the pore structure may not be maintained. Therefore, the upper limit temperature of the heat treatment (H2 treatment) is appropriately determined within a range in which the decomposition of the porous carbon does not substantially occur and the pore structure can be maintained. When the porous carbon is mesoporous carbon, the upper limit temperature of the heat treatment (H2 treatment) is 800°C or less, preferably 750°C or less.
[0079] Another example of a suitable heat treatment method is a treatment in which the heat treatment in step (2) is carried out in an inert gas atmosphere. As the inert gas, nitrogen, helium, argon, etc. can be used, with argon being preferred.
[0080] The heat treatment temperature in an inert gas atmosphere is preferably 1100° C. or higher, 1150° C. or higher, 1200° C. or higher, or 1250° C. or higher. As will be described later in the Examples, crystalline Ta2O5 is abundant up to a heat treatment temperature of 900° C. in an inert gas (Ar) atmosphere, whereas Ta2O5 decreases when the heat treatment temperature is increased to 1000° C., and oxygen-deficient TaO is generated when the heat treatment temperature is increased to 1100° C. Although the detailed reasons are not clear at this stage, an electrode material that can provide an electrode with excellent performance (particularly mass activity) can be obtained when the Ta oxide support contains TaO.
[0081] Moreover, since performance decreases if the temperature becomes too high in an inert gas atmosphere, the upper limit of the heat treatment (inert gas treatment) temperature is 1400° C. or lower, and preferably 1350° C. or lower.
[0082] Step (3) is a step in which the porous composite support obtained in step (2) (porous carbon having a Ta oxide support fixed to the inner and outer pore surfaces) is mixed with a solution containing an electrode catalyst precursor, and then the solvent is distilled off to obtain a dried product, which is then heat-treated to produce electrode catalyst particles.
[0083] In step (3), a dried product is first obtained in which the electrode catalyst particle precursor is supported on the Ta oxide support in the porous composite support. The electrode catalyst particles supported on the porous composite support contained in the dried product may contain non-stoichiometric metal oxides and have low activity as is, so the electrochemical catalytic action of the metal that becomes the electrode catalyst is activated by heat treatment in an inert atmosphere such as nitrogen or argon, or in a reducing atmosphere containing hydrogen.
[0084] The electrode catalyst precursor in step (3) is not limited as long as it does not impair the object of the present invention. However, depending on the electrode catalyst precursor, the object of the present invention may not be achieved in terms of the particle size or dispersibility of the electrode metal particles.
[0085] Suitable methods capable of obtaining highly dispersed electrode catalyst particles having a small particle size include the noble metal acetylacetonate method using a noble metal acetylacetonate and the colloid method using a noble metal colloid, which will be described below.
[0086] The method of using a noble metal acetylacetonate as an electrode catalyst precursor (noble metal acetylacetonate method) involves supporting the electrode catalyst precursor, a noble metal acetylacetonate, on porous carbon with Ta oxide attached, and then directly converting the electrode catalyst precursor into electrode catalyst particles. This method is expected to improve catalytic activity because the noble metal precursor does not contain residual impurities.
[0087] The acetylacetonate compound, which is the electrode catalyst precursor, is supported on the porous composite support and then directly converted into electrode catalyst particles. In this method, the electrode catalyst precursor does not contain residual impurities, so that the catalytic activity is expected to be improved. In the acetylacetonate method, the electrode catalyst precursor is supported by dispersing the porous composite support in a solution in which the acetylacetonate compound of the electrode catalyst is dissolved in a suitable solvent such as dichloromethane, stirring the solution, and distilling off the solvent. In this method, electrode catalyst particles with a uniform particle size distribution in nano-size can be supported in a highly dispersed manner. In addition, since no strong oxidizing agent or reducing agent is used in the solution, there is an advantage in that deterioration of the Ta oxide support and porous carbon constituting the porous composite support can be avoided.
[0088] The acetylacetonate compound of the electrode catalyst includes precious metal acetylacetonates such as Pt, Ru, Ir, Pd, Rh, Os, Au, Ag, etc., and one or more of these can be used. The solvent may be any organic solvent capable of dispersing the precious metal acetylacetonate, and representative examples include dichloromethane and acetylacetone.
[0089] A method for supporting electrode catalyst particles using the acetylacetonate method is to place porous carbon supporting a Ta oxide carrier and a precious metal acetylacetonate in a designated container, and while cooling with ice, stir with an ultrasonic stirrer until all of the solvent has evaporated.
[0090] The heat treatment conditions are appropriately selected depending on the type of Ta oxide support, metal, and precursor that will be the electrode catalyst. For example, the heat treatment temperature is 180 to 400°C, preferably 200 to 250°C. If the temperature is too low, the activation of the metal that will be the electrode catalyst will be insufficient, and if the temperature is too high, the electrode catalyst particles will aggregate, resulting in a problem of an excessively small effective reaction surface area. Water vapor may be added to the atmosphere as necessary.
[0091] In addition, since the noble metal acetylacetonate method uses an organic solvent, the selectivity of supporting electrode catalyst particles on Ta oxide is slightly inferior compared to the colloidal method using an aqueous solvent described below. However, it is useful in that it can easily support highly dispersed electrode catalyst particles.
[0092] On the other hand, the colloidal method is a method that can obtain electrode catalyst particles with a narrow particle size distribution by using an aqueous solvent without using an organic solvent, which is essential in the noble metal acetylacetonate method. The colloidal method is advantageous over the supporting methods that require an organic solvent in that water can be used as the solvent. Since the colloidal method uses water as the solvent, the generated electrode catalyst particles are particularly difficult to support on hydrophobic porous carbon, and are therefore more likely to be selectively supported on the surface of Ta oxide. For example, when a Ta oxide with a high surface area is formed by the microwave heating uniform precipitation method, the colloidal method can be used to selectively support a highly dispersed electrode catalyst on the surface of the Ta oxide.
[0093] The colloid method is explained below. The colloid method is a method in which porous carbon with Ta oxide fixed thereto is dispersed in a solution containing an electrode catalyst precursor colloid (particularly a precious metal colloid), and the electrode catalyst precursor colloid is reduced and supported on the Ta oxide as electrode catalyst particles. The colloid method can produce electrode metal particles with a uniform nano-sized particle size distribution without using surfactants or organic solvents.
[0094] A specific example of the colloid method is to disperse Ta oxide-attached porous carbon in a solution containing a precious metal colloid, and reduce the precious metal colloid to support it on the Ta oxide as precious metal particles. The conditions for preparing the solution containing the precious metal colloid are not particularly limited, and may be appropriate depending on the selected precious metal precursor and reducing agent.
[0095] Examples of the solvent include water and lower alcohols such as methanol, ethanol, etc. One of the advantages of the colloidal method is that water can be used as a solvent.
[0096] Examples of reducing agents include sodium hydrogen sulfite (NaHSO3), sodium borohydride, sodium triethylborohydride, hydrogen peroxide, and hydrazine. These may be used alone or in combination of two or more. Furthermore, reduction may be performed with one reducing agent, and then reduction may be performed with another reducing agent. By performing such a multi-stage reduction treatment in the liquid phase, highly dispersed precious metal particles can be supported on the support. A preferred example of this method is to use the reducing agents NaHSO3 and hydrogen peroxide in that order.
[0097] The pH of the solution is particularly preferably pH 4 to 6. When the solution is prepared in this pH range, a colloidal solution in which the precious metal colloid is uniformly dispersed without aggregation can be prepared. The preferred temperature range is 20 to 100°C (particularly preferably 50 to 70°C). In addition, contact with the reducing agent for a long period of time increases the particle size of the formed precious metal particles, so the contact time is usually about 10 minutes to 2 hours.
[0098] Although the manufacturing method of the electrode material of the present invention has been described above, these are merely examples of the present invention, and various configurations other than those described above may also be adopted. The embodiments disclosed herein are illustrative in all respects and are not limiting.
[0099] <3. Electrode> The electrode of the present invention includes the above-mentioned electrode material of the present invention and a proton-conductive electrolyte material. In the electrode of the present invention, the electrode materials of the present invention are in contact with each other to form a conductive path.
[0100] A fuel cell electrode formed using the electrode material of the present invention will be described below. Specifically, the case where the above-mentioned electrode material is used as an electrode in a PEFC will be described.
[0101] This fuel cell electrode may be composed of only the above-mentioned electrode material, but usually contains a proton-conductive electrolyte material used in the electrolyte of the fuel cell (hereinafter, sometimes referred to as "proton-conductive electrolyte material" or simply "electrolyte material"). The electrolyte material contained in the fuel cell electrode together with the electrode material may be the same as or different from the electrolyte material used in the electrolyte membrane for the fuel cell. From the viewpoint of improving the adhesion between the fuel cell electrode and the electrolyte membrane, it is preferable to use the same one.
[0102] Proton-conductive electrolyte materials are used as electrolyte materials for the electrodes and electrolyte membranes of PEFCs. These proton-conductive electrolyte materials are roughly divided into fluorine-based electrolyte materials that contain fluorine atoms in all or part of the polymer backbone, and hydrocarbon-based electrolyte materials that do not contain fluorine atoms in the polymer backbone, and both of these can be used as electrolyte materials.
[0103] Specific preferred examples of fluorine-based electrolyte materials include Nafion (registered trademark, manufactured by DuPont), Aciplex (registered trademark, manufactured by Asahi Kasei Corporation), and Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.).
[0104] Specific examples of suitable hydrocarbon electrolyte materials include polymers such as polysulfonic acid, polystyrene sulfonic acid, polyaryl ether ketone sulfonic acid, polyphenyl sulfonic acid, polybenzimidazole sulfonic acid, polybenzimidazole phosphonic acid, and polyimide sulfonic acid, as well as polymers having side chains such as alkyl groups.
[0105] The mass ratio of the electrode material and the electrolyte material mixed with the electrode material may be appropriately determined so as to provide good proton conductivity in the electrode formed using these materials and to smoothly diffuse gas and discharge water vapor in the electrode. However, if the amount of electrolyte material mixed with the electrode material is too large, the proton conductivity is improved but the gas diffusibility is reduced. Conversely, if the amount of electrolyte material mixed is too small, the gas diffusibility is improved but the proton conductivity is reduced. Therefore, the mass ratio of the electrolyte material to the electrode material is preferably in the range of 10 to 50 mass%. If this mass ratio is less than 10 mass%, the continuity of the electrolyte material having proton conductivity is deteriorated, and sufficient proton conductivity as an electrode for a fuel cell cannot be ensured. Conversely, if it is more than 50 mass%, the continuity of the electrode material is deteriorated, and sufficient electronic conductivity as an electrode for a fuel cell may not be obtained. Furthermore, the diffusibility of gas (oxygen, hydrogen, water vapor) inside the electrode may be reduced.
[0106] The electrode of the present invention may contain components other than the above-mentioned electrode materials and proton conductive materials, as long as the object of the present invention is not impaired. For example, the electrode material of the present invention may contain a conductive material other than the porous carbon (hereinafter, referred to as "another conductive material"), which may increase the number of conductive paths connecting the electrode materials and improve the conductivity of the electrode as a whole.
[0107] As the other conductive material, a known conductive material used in a fuel cell electrode can be used. Typically, it is a carbon-based conductive material, and any carbon material can be used as long as it does not impair the object of the present invention.
[0108] Although the electrode containing the electrode material of the present invention has been described as an electrode for PEFC, the electrode material can be used as an electrode for various fuel cells other than PEFC, such as alkaline fuel cells, phosphoric acid fuel cells, etc. The electrode material can also be suitably used as an electrode for a water electrolysis device using a polymer electrolyte membrane similar to that of PEFC. The electrode for a fuel cell containing the electrode material of the present invention has excellent electrochemical catalytic activity for oxygen reduction and hydrogen oxidation, and can be used as a cathode and an anode. In particular, the electrode has excellent electrochemical catalytic activity for oxygen reduction, and electrochemical oxidative decomposition of the conductive material, which is the carrier, does not occur under the operating conditions of the fuel cell, and therefore can be suitably used as a cathode.
[0109] <4. Membrane electrode assembly (MEA)> The membrane electrode assembly of the present invention is a membrane electrode assembly having a solid polymer electrolyte membrane, a cathode bonded to one side of the solid polymer electrolyte membrane, and an anode bonded to the other side of the solid polymer electrolyte membrane, wherein either or both of the cathode and the anode are the above-mentioned electrodes of the present invention.
[0110] As a preferred embodiment of the present invention, a membrane electrode assembly using a fuel cell electrode containing the electrode material of the present invention as a cathode will be described. Fig. 2 is a schematic diagram showing a cross-sectional structure of a membrane electrode assembly according to an embodiment of the present invention. As shown in Fig. 2, a membrane electrode assembly 10 has a structure in which a cathode 4 and an anode 5 are disposed facing a solid polymer electrolyte membrane 6.
[0111] The cathode 4 is composed of an electrode catalyst layer 4a and a gas diffusion layer 4b. The electrode of the present invention using the above-mentioned electrode material of the present invention can be used for the electrode catalyst layer 4a. The thickness of the electrode catalyst layer 4a is not particularly limited, but is, for example, 1 μm or more and 100 μm or less.
[0112] As the gas diffusion layer 4b, a conventionally known gas diffusion layer can be used. For example, a conductive carbon-based sheet-like member having a pore size distribution of about 100 nm to 90 μm, which has been conventionally used as a gas diffusion layer for PEFC, can be used. Preferably, carbon paper, carbon cloth, carbon nonwoven fabric, etc., which have been subjected to a water-repellent treatment can be used. Also, a sheet-like member other than a carbon-based material such as stainless steel can be used. The thickness of such a gas diffusion layer 4b is not particularly limited, but is usually about 50 μm to 1 mm. Also, the gas diffusion layer 4b may have a microporous layer on one side thereof, which is made of an aggregate of carbon fine particles having an average particle size of about 10 to 100 nm and a water-repellent material.
[0113] The anode 5 is composed of an electrode catalyst layer 5a and a gas diffusion layer 5b. As the anode 5, in addition to the electrode of the present invention, other known anodes can be used in the same manner. For example, an electrode in which an electrode catalyst layer 5a is formed on a gas diffusion layer 5b by applying and drying a dispersion of an electrode material carrying precious metal particles as a catalyst and an electrolyte material of a fuel cell on the surface of a conductive support made of a carbon-based material such as graphite, carbon black, activated carbon, carbon nanotube, or glassy carbon. The gas diffusion layer 5b of the anode 5 can be the same as the gas diffusion layer 4b described for the cathode 4.
[0114] A known electrolyte membrane for PEFC may be used as the solid polymer electrolyte membrane 6 so long as it has proton conductivity, chemical stability, and thermal stability. Although the thickness is exaggerated in FIG. 2, the thickness of the solid polymer electrolyte membrane 6 is usually about 0.007 to 0.05 mm in order to reduce the electrical resistance.
[0115] Examples of electrolyte materials constituting the solid polymer electrolyte membrane 6 include fluorine-based electrolyte materials and hydrocarbon-based electrolyte materials. In particular, electrolyte membranes formed from fluorine-based electrolyte materials are preferred because they have excellent heat resistance, chemical stability, etc. Specific examples of suitable materials include Nafion (registered trademark, manufactured by DuPont), Aciplex (registered trademark, manufactured by Asahi Kasei Corporation), and Flemion (registered trademark, manufactured by Asahi Glass Co., Ltd.).
[0116] Although the embodiments of the MEA of the present invention have been described above with reference to the drawings, these are merely examples of the present invention, and various configurations other than those described above can also be adopted.
[0117] <5. Polymer electrolyte fuel cell> The polymer electrolyte fuel cell (single cell) of the present invention comprises the membrane electrode assembly of the present invention, and generally has a structure in which the membrane electrode assembly is sandwiched between separators having gas flow paths formed therein.
[0118] 3 is a conceptual diagram showing a typical configuration of a polymer electrolyte fuel cell according to the present invention. As shown in FIG. 3, in a polymer electrolyte fuel cell 20, hydrogen is supplied to the anode 5, and (reaction 1) 2H2→ 4H + +4e - The protons (H + ) is supplied to the cathode 4 through the solid polymer electrolyte membrane 6, and the generated electrons are supplied to the cathode through the external circuit 21, resulting in (Reaction 2) O2 + 4H + +4e - →2H2O reacts with oxygen to produce water. This electrochemical reaction between the anode and cathode generates a potential difference between the two electrodes. In the polymer electrolyte fuel cell of the present invention, the components other than the membrane electrode assembly of the present invention are the same as those of known polymer electrolyte fuel cells, so detailed description will be omitted. In practice, a fuel cell stack is formed by stacking the solid polymer electrolyte fuel cell (single cell) of the present invention in a number appropriate for the power generation performance, and the stack is used by assembling other associated devices such as a gas supply device and a cooling device. EXAMPLES
[0119] The present invention will be described in more detail below with reference to examples, but the present invention is not limited thereto. In the description of electrode materials below, platinum may be abbreviated as "Pt", Ta oxide support as "TaOx", and mesoporous carbon as "MC".
[0120] The porous carbon, Ta raw material compound, and noble metal precursor compound used are as follows. <Porous carbon> As the porous carbon, the following mesoporous carbon (MC) (manufactured by Toyo Tanso Co., Ltd., "Porous Carbon C Novel MJ(4)010 (grade name)") was used. Designed pore diameter: 10 nm Specific surface area: 1100 m 2 / g Total pore volume: 2.0 mL / g Micropore volume: 0.4 mL / g Particle size: 100 mesh pass (used after pulverization) <Ta raw material compound> As the Ta raw material compound, tantalum ethoxide (Ta(OC2H5)4, High Purity Chemical Research Institute Co., Ltd.) was used. <Noble metal precursor compound> As the noble metal precursor compound, Pt acetylacetonate (Pt(C5H7O2)2, Platinum(II) acetylacetonate, 97%, Sigma Aldrich) was used. In some cases, Pt acetylacetonate will be hereinafter referred to as Pt precursor (Pt(acac)2).
[0121] 1. Preparation of electrode material The electrode materials of the following experimental examples were manufactured.
[0122] 1-1. Preparation of electrode material (without supported electrode catalyst) As shown in the flowchart of Figure 4, the electrode materials (without supported electrode catalyst) of Experimental Examples 1 to 11 were prepared by the steam hydrolysis method. First, 50 mg of the above mesoporous carbon (MC) as the support skeleton was pulverized in a ball mill to a particle size of about 1 μm, and then dispersed in an organic solvent (a mixture of acetylacetone and toluene in a volume ratio of 2:1) to obtain a dispersion containing MC. Next, a tantalum ethoxide reagent was dissolved in an organic solvent (ethanol) to prepare a metal ethoxide solution containing 35 wt% Ta. This metal ethoxide solution was added to the dispersion containing MC, and the total amount of solvent was adjusted to 50 mL. The pressure was reduced while ultrasonic stirring, and the organic solvent was evaporated to obtain a dry powder in which the metal ethoxide reagent was uniformly adsorbed on the MC surface (inner and outer surfaces of the pores).
[0123] (H2 treatment) The obtained dried powder was pulverized and then held in a water vapor nitrogen atmosphere (3% humidified N2 atmosphere) at 30°C for 1 hour to promote water vapor hydrolysis of the metal ethoxide reagent, and then heated to 400°C in a nitrogen atmosphere and held for 2 hours, and further heated to 800°C in a nitrogen atmosphere and held for 30 minutes. After that, the material was held in a hydrogen atmosphere at a predetermined temperature for a predetermined time and heat-treated (H2 treatment) to produce electrode materials (TaOx / MC, H2 treatment) of Experimental Examples 1 to 4. Table 1 shows the heat treatment conditions during the preparation of the electrode materials (TaOx / MC, H2 treatment) in Experimental Examples 1 to 4.
[0124] (Ar treatment) The obtained dried powder was pulverized and then held in a 30°C water vapor Ar atmosphere (3% humidified Ar atmosphere) for 1 hour to promote steam hydrolysis of the metal ethoxide reagent, and then heated to 400°C in an Ar atmosphere and held for 2 hours, and further heated to 800°C in an Ar atmosphere and held for 30 minutes. Thereafter, the material was held in an Ar atmosphere at a predetermined temperature for a predetermined time for heat treatment (Ar treatment) to produce electrode materials (TaOx / MC, Ar treatment) of Experimental Examples 5 to 11. Table 4 shows the heat treatment conditions during the preparation of the electrode materials (TaOx / MC, Ar treatment) in Experimental Examples 5 to 11.
[0125] [Table 1]
[0126] 1-2. Preparation of electrode material (with electrode catalyst support) Next, according to the flow chart shown in FIG. 5, an electrode material (with electrode catalyst support) of an experimental example was produced. Pt catalyst particles, which are electrode catalyst particles, were supported by the platinum acetylacetonate method on the electrode materials (electrode catalyst unsupported) of Experimental Examples 1 to 11. The amount of Pt precursor (Pt(acac)2) was adjusted so that Pt was 32 wt %. The electrode material (electrode catalyst unsupported) of Experimental Examples 1 to 11, which is made of MC with Ta oxide support, and Pt precursor were added to an eggplant flask, and acetone was further added to dissolve. Next, while cooling the eggplant flask on ice, the mixture was stirred with an ultrasonic stirrer until the solvent was completely evaporated to obtain a dry powder. Next, the obtained dry powder was subjected to reduction treatment at 210°C for 3 hours and at 240°C for 3 hours in a N2 atmosphere to obtain the electrode material (Pt / TaOx / MC) of Experimental Examples 1 to 11.
[0127] <Comparative Example> As a comparative example, an electrode material (Pt / MC) in which Pt was directly supported on MC was obtained in the same manner as in the experimental example, except that an MC to which no Ta oxide support was fixed was used.
[0128] <Reference example> As a reference example, a commercially available platinum-supported carbon black catalyst (Pt / C, (Tanaka Kikinzoku Kogyo Co., Ltd., TEC10E50E) was used.
[0129] 2. Physical property evaluation <Electrode materials of Experimental Examples 1 to 4 (electrode catalyst not supported, H2 treatment)> X-ray diffraction measurements were carried out on the electrode materials (electrode catalyst unsupported, H2 treatment) of Experimental Examples 1 to 4. FIG. As shown in Figure 6, no crystalline signal was observed in Experimental Example 1 (500°C), but a Ta2O5 signal was observed in Experimental Example 2 (600°C), and it was confirmed that the crystallinity of Ta2O5 increased with increasing treatment temperature in Experimental Example 3 (700°C) and Experimental Example 4 (800°C). On the other hand, no metallic Ta signal was observed.
[0130] The microstructures of the electrode materials (without supporting an electrode catalyst) of Experimental Examples 1 to 4 were observed. 7 to 10 show FESEM images of Experimental Examples 1 to 4, FIG. 11 shows a STEM image of Experimental Example 3 (electrode catalyst not supported), and FIG. 12 shows energy dispersive X-ray analysis (EDS) mapping and selected area electron diffraction pattern (SAEDP) of Experimental Example 2, respectively.
[0131] 7 to 10, it was confirmed that 2 to 3 nm TaOx particles were highly dispersed (fixed) in Experimental Examples 1 to 3. In Experimental Example 4 (H2 treatment at 800°C), it was confirmed that the structure of the MC, which is the carbon support, was destroyed because the carbon surface was smooth. In addition, STEM evaluation confirmed that TaOx exists in the pores of the electrode material (TaOx / MC) of the experimental example. A representative STEM image of Experimental Example 3 (H2 treatment at 700°C) is shown in Figure 11. In addition, no clear Ta peak was observed in the SAEDP of Experimental Example 3 (H2 treatment at 700°C) shown in Figure 12, suggesting that Ta exists in an amorphous state.
[0132] <Electrode materials of Experimental Examples 5 to 11 (electrode catalyst not supported, Ar treatment)> X-ray diffraction measurements were carried out on the electrode materials (electrode catalyst unsupported, Ar treatment) of Experimental Examples 5 to 11. The XRD profiles of Experimental Examples 5 to 11 are shown in FIG. As shown in FIG. 13, a peak derived from crystalline Ta2O5 was observed in the case of Ar treatment at 800°C (Experimental Example 5), and an increase in the peak was confirmed up to Ar treatment at 900°C (Experimental Example 6). This confirmed that the crystallinity of Ta2O5 improves up to Ar treatment at 900°C. On the other hand, when the Ar treatment was performed at 1000°C (Experimental Example 7), the peaks derived from Ta2O5 decreased, and when the temperature was increased to 1100°C (Experimental Example 8), the peaks derived from Ta2O5 were hardly observed. Furthermore, in the case of Ar treatment at 1200°C (Experimental Example 9), the generation of crystalline TaO was confirmed, and in the case of Ar treatment at 1300°C (Experimental Example 10), an increase in the peak derived from TaO was confirmed, confirming that the crystallinity of TaO was improved. From this, it was determined that when Ar treatment is performed at 1100°C or higher, the carbon that makes up the porous carbon (MC) acts as a reducing agent, reducing Ta2O5 and producing oxygen-deficient TaO, and that further increasing the temperature improves the crystallinity of the TaO.
[0133] The microstructures of the electrode materials (without supporting an electrode catalyst) of Experimental Examples 5 to 11 were observed. As representative examples, FESEM images of Ar treatment at 900°C (Experimental Example 6), Ar treatment at 1100°C (Experimental Example 8), and Ar treatment at 1300°C (Experimental Example 10) are shown in Figures 14 to 16. 14 to 16, the FESEM images show that the particle size of TaOx particles increases with increasing temperature. Also, as shown in Fig. 16, it was confirmed that the porous carbon (MC) structure of the electrode material of Experimental Example 10 was not destroyed despite being heat-treated at 1300°C.
[0134] Regarding the Ar treatment at 1300° C. (Experimental Example 10), FIG. 17 shows the results of EDS mapping and SAEDP, and FIG. 18 shows the results of EDS line analysis. From Fig. 17, it was confirmed that crystalline TaO particles with a particle size of about 2 to 10 nm were dispersed. As a result of EDS line analysis of the TaO particles shown in Fig. 18, it was found that the TaOx in the center had an x value of less than 1, and the TaOx on the surface had an x value of more than 1.
[0135] 3. Electrochemical evaluation (half cell) 3-1. Initial activity evaluation 3-1-1. Cyclic voltammetry (CV) evaluation The electrode materials of Experimental Examples 1 to 11 (Pt / TaOx / MC), Comparative Example (Pt / MC), and Reference Example (Pt / C) were evaluated by cyclic voltammetry (CV). The electrochemical surface area (ECSA) was calculated from the amount of hydrogen adsorption determined by CV. The ECSA corresponds to the effective surface area of Pt contained in the electrode material.
[0136] The fuel cell electrodes for evaluation were prepared in the following manner. First, a mixed solution of 19 mL of ultrapure water and 6 mL of 2-propanol was added to a sample bottle containing the electrode material powder, followed by the addition of 100 μL of 5% Nafion dispersion. The sample bottle was then immersed in ice water and ultrasonically stirred for 30 minutes to obtain an electrode material dispersion. The amount of electrode material powder was determined based on the amount of Pt per unit area on the electrode when 10 μL of the electrode material dispersion was dropped onto the electrode. -Pt / cm 2 10 μL of the prepared electrode material dispersion was dropped onto the Au disk electrode using a micropipette and placed in an incubator and dried at 60° C. for about 15 minutes to form a Nafion membrane and fix the electrode material onto the Au electrode, thereby obtaining a fuel cell electrode (working electrode) for evaluation.
[0137] The CV measurement conditions are as follows. Assuming that one atom of H is adsorbed per one atom of Pt, the CV is 210 μC / cm 2 This results in an electrical charge of Measurement: Three-electrode cell (working electrode: fuel cell electrode for evaluation, counter electrode: Pt, reference electrode: Ag / AgCl) Electrolyte: 0.1M HClO4 (pH: approx. 1) Measurement potential range: 0.05 to 1.2 V (based on the reversible hydrogen electrode) Scan speed: 50 mV / s Amount of hydrogen adsorption: Calculated from the peak area showing hydrogen adsorption at 0.05 to 0.4 V Electrochemical surface area (ECSA): Calculated using the following formula ECSA=(hydrogen adsorption amount)[μC] / 210[μC / cm 2 ]
[0138] In the cyclic voltammograms (not shown) of the electrodes using the electrode materials of Experimental Examples 1 to 11, peaks (0.05 to 0.4 V) due to the adsorption and desorption of hydrogen originating from Pt were observed, confirming that they function as electrodes for fuel cells.
[0139] The electrochemical surface area (ECSA) of the electrodes using the electrode materials (H2 treatment) of Experimental Examples 1 to 4 is shown in Fig. 19, and the electrode materials (Ar treatment) of Experimental Examples 5 to 11 are shown in Fig. 20. Table 2 summarizes the ECSA values of the electrodes using each electrode material. As shown in Figures 19 and 20 and Table 2, it was confirmed that the ECSA of the electrode materials of Experimental Examples 1 to 11 (Pt / TaOx / MC) was larger than that of the electrode material of the comparative example (Pt / MC) and was equal to or greater than that of the electrode material of the reference example (Pt / C, TEC10E50E).
[0140] [Table 2]
[0141] 3-1-2. Evaluation of oxygen reduction reaction (ORR) activity The electrode materials of Experimental Examples 1 to 11, the Comparative Example, and the Reference Example were evaluated for ORR activity. ORR activity was measured by linear sweep voltammetry (LSV) using the rotating disk electrode (RDE) method, and the activation-dominant current (i k ) was used as an index. Mass activity = i k / mass of Pt on electrode Activation dominant current (i k ) is the current-potential curve obtained by rotating electrode measurement at any potential i -1 and ω -1 / 2 A Koutecky-Levich plot was created by plotting the above-mentioned line, and the intercept was determined by extrapolating the obtained line. The specific procedure is as follows: First, O2 was bubbled at 50 mL / min for 30 min, and then 0.2 V RHE 1.20 V at 10 mV / s in the positive direction RHE The potential was scanned up to 1000 V, and the measurements were performed. During the measurements, O2 was constantly purged at 50 mL / min. RHE is the potential relative to the reversible hydrogen electrode (RHE).
[0142] FIG. 21 shows the mass activity (0.9V) of the electrodes using the electrode materials of Experimental Examples 1 to 4 (H2 treatment), and FIG. 22 shows the mass activity (0.9V) of the electrodes using the electrode materials of Experimental Examples 5 to 11 (Ar treatment). RHE ) is shown. Table 3 shows the mass activity values for electrodes using each electrode material. As shown in Fig. 21, in the electrode materials (H2 treatment) of Experimental Examples 1 to 4, the activity improved as the H2 treatment temperature was increased from 500°C, and the highest activity was observed at 700°C (Experimental Example 4). On the other hand, a decrease in activity was confirmed when the temperature was increased to 800°C. It was determined that the collapse of the skeleton of the porous carbon (MC) contributed to the decrease in activity. 22, in the electrode materials (Ar treatment) of Experimental Examples 5 to 11, the activity improved as the Ar treatment temperature was increased from 800°C, and the highest activity was observed at 1300°C (Experimental Example 10). The decrease in activity at 1400°C (Experimental Example 11) was determined to be due to a change in the MC structure caused by the high-temperature treatment.
[0143] [Table 3]
[0144] 3-2. Start-stop cycle test A start-stop cycle test was conducted for the electrode materials of Experimental Example 3 (H2 treatment, 700°C), Experimental Example 10 (Ar treatment, 1300°C), and Comparative Example (Pt / MC) using the method recommended by the Fuel Cell Commercialization Council of Japan (FCCJ) (Proposal of the Goals, Research and Development Issues, and Evaluation Methods for Polymer Electrolyte Fuel Cells, published in January 2011). The start-stop cycle test is a cycle test that promotes carbon corrosion, and specifically, the start-stop cycle test is conducted at 1.0 to 1.5 V as shown in Figure 23. RHEThis square wave is applied for 2 seconds per cycle, and the deterioration behavior of the electrode catalyst after the cycle test is evaluated as the ECSA retention rate.
[0145] FIG. 24 shows the ECSA retention rates of the electrodes using the electrode materials of Experimental Example 3, Experimental Example 10, and the Comparative Example in a start-stop cycle test (up to 60,000 cycles). As shown in FIG. 24, in the comparative example (Pt / MC), the ECSA retention rate decreased significantly with the start-stop cycles, reaching nearly 0% at 5000 cycles, whereas experimental example 3 (H2 treatment, 700°C) and experimental example 10 (Ar treatment, 1300°C) maintained a high ECSA retention rate. Up to 30,000 cycles, the ECSA retention rate of Experimental Example 3 (H2 treatment, 700°C) was higher than that of Experimental Example 10 (Ar treatment, 1300°C). However, after 30,000 cycles, the relationship was reversed, and at 60,000 cycles, Experimental Example 10 had a higher ECSA retention rate (ECSA retention rate of Experimental Example 3: 8%, Experimental Example 10: 17%). In this way, it was confirmed that the electrode material of the experimental example (Pt / TaOx / MC) had significantly improved durability compared to the comparative example (Pt / MC). From this, it was determined that the presence of TaOx particles fixed to the MC, which is porous carbon, inhibits direct contact between the Pt particles and the MC, effectively preventing carbon corrosion and suppressing the aggregation and detachment of the Pt particles.
[0146] 2-3. Load change cycle test A load change cycle durability test was conducted on the electrode materials of Experimental Example 3 (H2 treatment, 700°C), Experimental Example 10 (Ar treatment, 1300°C), and Reference Example (Pt / C). The load change cycle test was conducted by applying a potential cycle simulating a load change according to the method recommended by the Fuel Cell Commercialization Promotion Council of Japan (FCCJ) (Proposal of Goals, Research and Development Issues, and Evaluation Methods for Polymer Electrolyte Fuel Cells, published in May 2023). The load change cycle shown in Figure 25 is a cycle that promotes deterioration accompanied by dissolution and redeposition of the catalyst itself, and is a cycle of 0.6 to 0.95 V RHE The experiment was conducted by applying a square wave of 1000mV for 6 seconds, with 3 seconds per cycle, and measuring the changes in ECSA and LSV before and after the load change cycle test.
[0147] FIG. 26 shows the ECSA retention rates of electrodes using the electrode materials of Experimental Example 3, Experimental Example 10, and Reference Example (Pt / C, TEC10E50E) in a load change cycle test (up to 100,000 cycles). The ECSA retention rate after the load change cycle test (100,000 cycles) was 74% for Experimental Example 3 (H2 treatment, 700°C) and 58% for Experimental Example 10 (Ar treatment, 1300°C), which were higher than the 44% of the Reference Example (Pt / C), which is the standard catalyst. Thus, in the load change cycle test, it was confirmed that the electrode materials of Experimental Examples 3 and 10 have dramatically improved durability compared to the electrode material of the Reference Example, which is the standard catalyst for fuel cells. In addition, when the LSV changes of the electrode materials of Experimental Examples 3 and 10 before and after the load change cycle test (100,000 cycles) were evaluated (not shown), it was confirmed that the negative shift of the LSV curve was suppressed to some extent and activity could be maintained even after 100,000 cycles.
[0148] The electrode materials of Experimental Examples 3 and 10 were observed with a transmission electron microscope (TEM) after the load change cycle test (100,000 cycles). As shown in Figures 27 and 28, it was confirmed that the Pt fine particles remained without agglomeration in both Experimental Example 3 and Experimental Example 10. Therefore, it was determined that the mesopores suppress the aggregation of Pt. [Industrial Applicability]
[0149] The electrode material of the present invention can provide a fuel cell electrode having excellent electrocatalytic activity, electronic conductivity, gas diffusibility, and excellent durability, and is promising as an electrode component of a polymer electrolyte fuel cell used in the automobile, electric power, gas, and home appliance industries. It is particularly expected to be used for fuel cell automobiles (passenger cars and commercial vehicles) that are subject to large load fluctuations. [Explanation of symbols]
[0150] 1 Electrode material 2. Porous carbon 2a Pore inner surface 2b Outer surface 3 Electrocatalyst composite 3a Ta oxide support 3b Electrocatalyst particles 4. Fuel cell electrodes (cathode) 4a Electrode catalyst layer (cathode) 4b Gas diffusion layer 5. Fuel cell electrodes (anodes) 5a Electrode catalyst layer (anode) 5b Gas diffusion layer 6 Solid polymer electrolyte membrane 10 Membrane electrode assembly (MEA) 20 Polymer electrolyte fuel cell 21 External circuit P pore
Claims
1. The present invention includes a porous composite support including a support skeleton made of porous carbon, a Ta oxide support fixed to at least the inner pore surface of the inner pore surface and the outer pore surface of the porous carbon, and electrode catalyst particles supported on the porous composite support, 13. An electrode material, comprising: a part or all of the electrode catalyst particles supported within the pores of the porous carbon via the Ta oxide support.
2. The electrode material according to claim 1 , wherein the Ta oxide support comprises a crystalline Ta oxide.
3. 3. The electrode material according to claim 2, wherein the Ta oxide support is a Ta oxide support containing an oxygen-deficient Ta oxide.
4. 4. The electrode material according to claim 3, wherein the Ta oxide support is a Ta oxide support containing TaO.
5. 2. The electrode material according to claim 1, wherein the porous carbon is mesoporous carbon.
6. 6. The electrode material according to claim 5, wherein the pore diameter of the mesoporous carbon is 3 nm or more and 40 nm or less.
7. 2. The electrode material according to claim 1, wherein the electrode catalyst particles are particles made of Pt or an alloy containing Pt.
8. An electrode comprising the electrode material according to claim 1 and a proton-conducting electrolyte material.
9. 9. A membrane electrode assembly comprising a solid polymer electrolyte membrane, a cathode bonded to one side of the solid polymer electrolyte membrane, and an anode bonded to the other side of the solid polymer electrolyte membrane, wherein either or both of the anode and the cathode are the electrodes according to claim 8.
10. A polymer electrolyte fuel cell comprising the membrane electrode assembly according to claim 9.
11. A method for producing the electrode material according to claim 1, comprising the following steps (1) to (3): Step (1): A step of mixing porous carbon and tantalum alkoxide in a non-aqueous organic solvent, and then distilling off the solvent to obtain a dried product in which tantalum alkoxide is fixed to the inner and outer pore surfaces of the porous carbon. Step (2): A step of hydrolyzing the tantalum alkoxide by steam-treating the dried product obtained in step (1), and then heat-treating the product to obtain a porous composite support in which the Ta oxide support is fixed to the inner and outer pore surfaces of the porous carbon. Step (3): A step of mixing the porous composite support obtained in step (2) with a solution containing an electrode catalyst precursor, and then heat-treating the dried product obtained by distilling off the solvent to produce electrode catalyst particles.
Citation Information
Patent Citations
Anode electrode material for fuel battery, method of manufacturing the same, electrode for fuel battery, membrane electrode assembly, and solid polymer type fuel battery
JP2015195193A
Catalyst layer ink and manufacturing method of fuel cell
JP2019207789A
Electrode catalyst for electrochemical device, electrode catalyst layer for electrochemical device, membrane / electrode assembly for electrochemical device, electrochemical device, manufacturing method of electrode catalyst for electrochemical device, and manufacturing method of membrane / electrode assembly for electrochemical device
JP2020064852A
Fuel cell catalyst
JP2020126816A
Manufacturing method of electrode material
JP2020161273A